Owner power, deliberate strategy formulation, and strategic management accounting - Ari Kuncara Widagdo, Antonius Singgih Setiawan, Rahmawati Rahmawati, Djuminah Djuminah, (Opción, 2019)
This research was conducted to identify the correlation between hotel owner power over the strategy formulation preference and the implementation of strategic management accounting, with the application of the sequential mixed-method approach. In the qualitative phase, 11 hotel managers and 2 hotel owners were interviewed. The result of the research demonstrates that a no controlling owner power will promote deliberate strategy formulation and the implementation of strategic management accounting. In conclusion, the preference of deliberate strategy formulation will promote the implementation of strategic management accounting on a larger scale.